Suppressing MicroRNA-30b by Estrogen Promotes Osteogenesis in Bone Marrow Mesenchymal Stem Cells. (4th April 2019) - Liu, Guanqi; Lu, Yeming; Mai, Zhihui; Liu, Runheng; Peng, Zhuli; Chen, Lin; Chen, Zheng; Wang, Ruizhi; Ai, Hong
Abstract : MicroRNAs (miRNAs) have been widely demonstrated to interact with multiple cellular signaling pathways and to participate in a wide range of physiological processes. Estradiol-17 β (E2) is the most potent and prevalent endogenous estrogen that plays a vital role in promoting bone formation and reducing bone resorption. Currently, little is known about the regulation of miRNAs in E2-induced osteogenic differentiation. In the present study, the primary bone marrow mesenchymal stem cells from rats (rBMSCs) were isolated and incubated with E2, followed by miRNA profiling. The microarray showed that 29 miRNAs were differentially expressed in response to E2 stimulation. Further verification by real-time reverse-transcriptase polymerase chain reaction revealed that E2 enhanced the expression of let-7b and miR-25 but suppressed the miR-30b expression. Moreover, a gain-of-function experiment confirmed that miR-30b negatively regulated the E2-induced osteogenic differentiation. These data suggest an important role of miRNAs in osteogenic differentiation.